Enhanced zinc ions storage performance by calcium ion induction/anchoring of vanadium-based nanobelts at low temperature. (November 2022) - Fan, L.; Cao, L.; Xiong, S.; Wu, Y.; Li, Z.; Gu, F.
Abstract: Low-cost, high abundance, environmentally friendly, and intrinsic safety endow the aqueous Zn ion batteries a bright prospect for large-scale energy storage. However, it is still challenging to find suitable cathode materials with excellent Zn 2+ ion storage performance due to sluggish Zn 2+ ions intercalation kinetics. Herein, we prepare the novel nanobelts as advanced cathode materials via a simple solution impregnation method. Firstly, the Ca 2+ ions promote the conversion of vanadium-based materials from nanoparticles to nanobelts, and also act as a pillar to stabilize the structure of the vanadium-based material. Furthermore, the amorphous structure of the electrode also can be tuned by subsequent appropriate calcination, aiming to enhance Zn-storage performances. Thus, the cathode materials exhibit the superior electrochemical performances with a high-capacity retention rate of 93.75% at 0.5 A/g after 100 cycles and a capacity retention rate of 91.3% after 3000 cycles at 5 A/g. In addition, the flexible quasi-solid-state Zn ion batteries with Ca 2+ ions pre-intercalated vanadium-based oxide as cathode is also investigated, and show stable electrochemical properties under bending states. With the cost-effective and green large-scale synthesis process, the outstanding electrochemical performance of cathode shed light on the rational design of novel cathodes for practical aqueous Zn ion batteries. Graphical abstract: Image 1 Highlights: A simple solution impregnation method at ambient conditions is proposed The conversion of vanadium-based materials from nanoparticles to nanobelts Amorphous structure of electrode also can enhance Zn-storage performances Soft-packaged battery exhibits promising electrochemical performance